2022
DOI: 10.1136/bmjopen-2022-062245
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced red blood cell distribution width to platelet ratio is a predictor of mortality in patients with sepsis: a propensity score matching analysis based on the MIMIC-IV database

Abstract: ObjectiveTo explore the association between dynamic changes in red blood cell distribution width to platelet count ratio (RPR) during hospitalisation and short-term mortality in patients with sepsis.DesignA retrospective cohort study using propensity score matching.SettingIntensive care units (ICUs) of Beth Israel Deaconess Medical Center.ParticipantsA total of 8731 adult patients with sepsis were included in the study. The patients were identified from the ICU of the Medical Information Mart for Intensive Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…The association of decreased platelet count with poor prognosis has been well supported in studies among different populations, especially in ICU patients 15 18 . Nihat Polat et al revealed that in patients with acute decompensated HF, baseline platelet counts were significantly higher in alive patients than in deceased patients, and lower platelet counts predicted an increased risk of death at one year 19 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The association of decreased platelet count with poor prognosis has been well supported in studies among different populations, especially in ICU patients 15 18 . Nihat Polat et al revealed that in patients with acute decompensated HF, baseline platelet counts were significantly higher in alive patients than in deceased patients, and lower platelet counts predicted an increased risk of death at one year 19 .…”
Section: Discussionmentioning
confidence: 81%
“…( 1234567890 www.nature.com/scientificreports/ sufficient adjustment for confounders, we found that the early decline in platelet counts was an independent predictor of in-hospital death in critical patients with AHF. The association of decreased platelet count with poor prognosis has been well supported in studies among different populations, especially in ICU patients [15][16][17][18] . Nihat Polat et al revealed that in patients with acute decompensated HF, baseline platelet counts were significantly higher in alive patients than in deceased patients, and lower platelet counts predicted an increased risk of death at one year 19 .…”
Section: Discussionmentioning
confidence: 82%
“…Extensive research has identified several indices predictive of sepsis outcomes, including the neutrophil-to-lymphocyte ratio, albumin levels, platelet count and the ratio of red blood cell distribution width (RDW) to platelet count. [5][6][7][8] RDW has emerged as a significant and reliable marker for acute and chronic systemic inflammation. 9 It measures…”
Section: Introductionmentioning
confidence: 99%